Mandatory pre-abortion counseling is a barrier to accessing safe abortion services - Bain, Luchuo Engelbert (Pan Afr Med J, 2020)
Empirical research showcases that pre-abortion counseling scarcely reverses the woman’s decision either to terminate a pregnancy or not. Growing evidence regarding the high levels of decisional certainty among women seeking abortions renders a careful rethink of the place of mandatory pre-abortion counseling packages. Mandatory counseling packages, when inscribed in the laws, at times contain false information that can deter women from going in for safe abortions. Mandatory waiting times indirectly label opting for an abortion as not being the right thing to do. In areas where abortion stigma from health care providers and communities remains highly prevalent, women are forced to incur extra expenses by travelling to other countries. I argue that pre-abortion counseling on opting-in grounds is ethically sound (enhances the woman’s reproductive autonomy), since most clients in need of abortions are certain on their decisions before the abortion care provider and do not regret these decisions after the process. Regrets are prone to be more prevalent in areas with high unsafe abortion practices, generally due to complications from excessive bleeding, pain, and post abortion infections. Allowing systematic mandatory pre-abortion counseling practice as the rule in a competent adult is unjustified ethically and empirically, is time consuming and presents the legality of abortions in most settings an oxymoron.